Women in Early America - Foster, Thomas A. (Book collections on Project MUSE., 2015)
Women in Early America, edited by Thomas A. Foster, tells the fascinating stories of the myriad women who shaped the early modern North American world from the colonial era through the first years of the Republic. This volume goes beyond the familiar stories of Pocahontas or Abigail Adams, recovering the lives and experiences of lesser-known women-both ordinary and elite, enslaved and free, Indigenous and immigrant-who lived and worked in not only British mainland America, but also New Spain, New France, New Netherlands, and the West Indies. In these essays we learn about the conditions tha.